An investigation on effects of perceived value on brand popularity and brand loyalty: A B2B case study - Zakaria Karimi Rad; Seyyed Majid Elahi; Morteza Gholami Tazeabad (Management Science Letters)
This research evaluates the effect of perceived value on brand popularity and brand loyalty for some organizations in business-to-business (B2B) domain under the effect of risk and e-service quality. The practical relationships among six different kinds of risks including performance, social, financial, time, psychological and safety with consideration of quality in e-commerce business on customer’s perceived value are evaluated and the effects of this perception of value on consequences of perceived value are measured. In this study, using the partial least square method as well as gathering the information of some Iranian firms that use electronic services, the study finds that there was a significant relationship between various types of risks and perceived value. There is also considerable influence of perceived value on satisfaction, brand popularity, and brand loyalty.